Penggunaan media kartu kata untuk meningkatkan Keterampilan membaca permulaan dan hasil belajar Bahasa indonesia siswa kelas I SD Katolik ST Fransiskus Xaverius Maumbi - Kasiahe, Evi Martika Dewi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This research aims to improve learning outcomes and initial reading skills using word card media for class I students at St Fransiskus Xaverius Maumbi Catholic Elementary School. This research is classroom action research. This research was carried out in Cycle II with 26 subjects. The improvement in reading skills can be seen from Cycle I. In cycle I, there were 2 students in the initial reading skills who received the very good category, and in the good category there were 10 students, while in the adequate category there were 4 students and in the poor category there were 10 students. So from the data from cycle I it can be seen that many class I students do not know how to read and pronounce words well. And in cycle II, initial reading skills showed an increase in each error. For cycle II there were 9 students who got the very good category, and for the good category there were 12 students while in the fair category there were 2 students and finally in the poor category there were 3 students. And the increase in learning outcomes can be seen in the achievement of completeness obtained by students. The average pre-cycle score was 61 with a percentage of 38%. After implementing cycle I the average score increased to 63 with a completion percentage of 46% and further increased in cycle II with an average score of 72 with a percentage of 80%.